MENINGKATKAN INTERAKSI DAN MOTIVASI BELAJAR IPS SISWA KELAS VII SMPN 1 KARANGPLOSO MELALUI TEKNIK STUDENT-CENTERED-LEARNING - Khumaidi Khumaidi (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2018)
The aim of this research is to see the increase of motivation and interaction in learning social sciences of SMP students.  This study took place at the SMPN 1 Karangploso Malang involving 30 seventh graders. This research used a classroom action research approach using two cycles and each cycle was conducted for three meetings.  The results show that scores on IPS increase substantially from cycle I to cycle II.  In addition, motivation and interaction that are elaborated into five indicators increase from 76% to 93%. The results are: appreciating friends’ contribution (76.7%), sharing the assignment with full responsibility (83.3%), asking query to the friend with full friendship (83.3%), giving assistance to review friends’ tasks (90%), and giving suggestions (62.3).  This result implies that cooperative learning gives maximum benefits to develop motivation and interaction in the classroom and the method is necessary to develop for other lessons.